Virals - Reichs, Kathy (New York : Razorbill, 2010)
Tory Brennan is the leader of a band of teenage 'sci- philes' who live on an island off the coast of South Carolina and when the group rescues a dog caged for medical testing, they are exposed to an experimental strain of canine parvovirus that changes their lives forever.
Keywords: Animal experimentation -- Juvenile fiction; Viruses -- Juvenile fiction; Science fiction